2021
DOI: 10.2147/ijgm.s331291
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis Patterns Correlate with Immune Microenvironment Characterization in Gastric Cancer

Abstract: Objective:We aimed to build a ferroptosis-based classifier to characterize the molecular features of gastric cancers (GC) and investigate the relationship between different ferroptosis patterns and GC tumor microenvironment (TME). Methods: Based on the genomic and clinical information from TCGA portal and GEO database, non-negative matrix factorization (NMF) was used to identify ferroptosis subtypes in GC patients. In order to estimate the ferroptosis levels, we established ferroptosis subtype score (FSS) to q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…In addition, a recent systematic review and meta-analysis demonstrated that promoting ferroptosis significantly benefits cancer prognosis [ 41 ]. Moreover, we observed a positive correlation between FS and IS in the COAD samples, a similar trend was also observed in other cancer types, such as gastric cancer [ 42 ]. Since the correlation between various immune cells in the TIME and ferroptosis of colon cancer cells is not well understood, we estimated the infiltration levels of immune cells in the tumor microenvironment of each sample.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, a recent systematic review and meta-analysis demonstrated that promoting ferroptosis significantly benefits cancer prognosis [ 41 ]. Moreover, we observed a positive correlation between FS and IS in the COAD samples, a similar trend was also observed in other cancer types, such as gastric cancer [ 42 ]. Since the correlation between various immune cells in the TIME and ferroptosis of colon cancer cells is not well understood, we estimated the infiltration levels of immune cells in the tumor microenvironment of each sample.…”
Section: Discussionsupporting
confidence: 83%
“…In the past year, dozens of bioinformatics articles investigated the correlation of FRG in cancers [23][24][25] For instance, Liang et al constructed a 10-FRG RS model that effectively predicted HCC patient prognosis in both discovery and validation cohorts, and showed that high-risk patients had attenuated antitumor immunity [23]. In this article, the difference was that we focused on FRSG, a set of genes related to ferroptosis as well as stemness.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis-related genes NOX4, CHAC1, and HIF1A were the prognostic biomarkers of gastric adenocarcinoma ( Xiao et al, 2022 ). In addition, it was also found that the ferroptosis pattern in GC is related to the characteristics of immune microenvironment ( Jiang X. et al, 2021 ; Liu S. J. et al, 2021 ; Wang F. et al, 2021 ). The establishment of markers associated with ferroptosis will help to predict the biological characteristics of GC and select the appropriate treatment for GC patients.…”
Section: Ferroptosis and Gastric Cancermentioning
confidence: 98%